Consumer analysis and the role of information in sustainable choices: A natural experiment - Caferra, Rocco; Imbert, Enrica; Schirone, Dario Antonio; Tiranzoni, Paola; Morone, Andrea (Frontiers in Environmental Economics, 2023)
Sustainable consumption (SC) is a key driver to accomplish urgent sustainability objectives and related targets. Indeed, the literature found increased evidence about the negative impact of the escalating level of consumption of goods and services by private consumers on the environment. Over the past years there have been several initiatives aimed at raising consumers awareness and education on SC. However, several studies show that an attitude change often does not translate into real behavior change. Accordingly, this paper investigates, through a natural field experiment, whether the consumer's behavior is influenced towards the purchase of sustainable products thanks to targeted communication. During the treatment phase, sustainable consumption preferences are elicited through ad-hoc on-site banner signals. The results show that consumers are influenced by sustainability issues and that on-site banner signs have an impact on the average expenditure of sustainable products aesthetically similar to conventional counterparts. Conversely, this was not the case for sustainable innovative products rather esthetically different. Overall, our work found that informative tools have a positive effect but seems to suggest that consumers are still not ready to switch to sustainable products when aesthetic characteristics are not up to their standards.